LAND USE POLICY AREA (LUPA) CONCEPT MODEL - A. M. R. Abante (Copernicus Publications, 2021)
The paper presents a Land Use Policy Area (LUPA) Concept Model adding the three basic elements: (i) ecosystem-based land use regarded as the intersection of the ecosystem and land use elements, (ii) subwatershed-based land use as the intersection of the subwatershed and land use elements, and (iii) integrated environmental management is the intersection of the subwatershed and ecosystem elements regarded as the Integrated Ecosystem Development Planning Unit (IE-DPU). The basic (spatial) elements are mathematically expressed as the paired sets of the three main variables, namely: ecosystem (dependent), watershed (dependent) and land use (independent) variables. The challenging work in this study was the development of a geospatial information model for use in policy areas LUPA applying these variables. There are four steps applied to answer the research objective, these are: ecological zone assessment, ridge-to-reef watershed delineation, land and water use heads-up mapping, ecosystem-based land use overlay analysis, watershed-based land use overlay analysis, integrated environmental management overlay analysis, and LUPA overlay analysis. The concept model analysis steers the geospatial information modeling for LUPA which carried the intersections of the paired variables: ecosystem-based land use, subwatershed-based land use and integrated environmental management as variating inputs to process by extracting the science-based information (overlay output) which practically highlighted the LUPA classification: (i) Protection with 49.1% or 3858.2 Ha of mangrove forest reserve and water use, (ii) Production areas with 46.5% or 3631.7 Ha mostly agricultural and aquacultural areas, (iii) Settlement with 2.7% or 209.2 Ha of urban and urban uses, and (iv) Infrastructure with 1.5% or 116.7 Ha of development. The authors concluded that land use policy areas will relatively change as land use changes which is also seen reliant on the impacts of climate change.